2020
DOI: 10.3390/pharmaceutics12020167
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mechanisms of Polymannuronic Acid and Polyguluronic Acid Across Caco-2 Cell Monolayers

Abstract: Detailed knowledge of the intestinal transport of polymannuronic acid (PM) and polyguluronic acid (PG) is critical for understanding their biological activities. To investigate the transport in the gastrointestinal tract, PM and PG were chemically modified with tyramine and conjugated with fluorescein isothiocyanate (FITC) to synthesize FITC-PM (F-PM) and FITC-PG (F-PG) successfully. The transport mechanisms of F-PM and F-PG across the intestinal epithelial cell monolayers (Caco-2 cell monolayers) were then in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…The Caco-2 ​cell monolayer model is widely used to mimic the absorption and transport of drugs across the intestinal epithelial layer ( Wang et al., 2020 ). The permeability of hydroxycinnamic acid derivatives and EZ in presence of cholesterol was studied by using the Caco-2 ​cell line differentiated as a monolayer, in a Transwell system.…”
Section: Resultsmentioning
confidence: 99%
“…The Caco-2 ​cell monolayer model is widely used to mimic the absorption and transport of drugs across the intestinal epithelial layer ( Wang et al., 2020 ). The permeability of hydroxycinnamic acid derivatives and EZ in presence of cholesterol was studied by using the Caco-2 ​cell line differentiated as a monolayer, in a Transwell system.…”
Section: Resultsmentioning
confidence: 99%
“…After loading 10 μL of sample into each hole, the voltage was set at 60 V, and electrophoresis was timed for 80 min. The gels were observed with a gel imager (Bio-RAD, Hercules, CA, USA) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Owing to a lack of chromophore and light-absorbing groups in PM, other biological components easily interfere with the detection of PM concentrations in vivo, which makes it difficult to establish an effective analytical method. In our previous study, PM was labeled with fluorescein isothiocyanate (FITC) to synthesize FITC-PM, detected the cytotoxicity by MTT, and then the PM-transport mechanism was studied using Caco-2 cell monolayer model [ 12 ]. The results of the study provided the first detailed information on the mechanisms of PM transport across intestinal epithelial cells in vitro: the PM had no measurable cytotoxicity, the transportation of PM in Caco-2 cells was a time-dependent and energy-dependent process with carrier saturation and efflux.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results by Liu et al showed that the stability constant of the complex formed with HPCD was enhanced after avanones are complexed with cyclodextrin [26] . Chitosan is a cationic polysaccharide with the function of adhering mucous membrane, which can reversibly open Caco-2 cells to promote drug absorption [27] , Ma et al prepared the HYA-CS complex, the bioavailability of HYA was increased by 4.76 times [28] . Lv et al also found that HYA is a Pglycoprotein substrate analog, which is easily excreted by P-glycoprotein in the intestinal tract, and leads to a strong bile e ux effect and low absorption [18] .…”
Section: Introductionmentioning
confidence: 99%